2019
DOI: 10.1097/sle.0000000000000645
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Results After Totally Robotic Restorative Total Proctocolectomy With Ileal Pouch Anal Anastomosis for Ulcerative Colitis

Abstract: In this study, we aimed to present our initial experience on totally robotic total restorative proctocolectomy in ulcerative colitis (UC) patients. Patients undergoing a totally robotic restorative total proctocolectomy with ileal J-pouch anal anastomosis for UC between January 2015 and November 2017 were included. The da Vinci Xi was used for the operations. Patient demographics, perioperative and short-term operative outcomes were evaluated. Ten patients were included. The median operative time was 380 minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Based on the quality assessment described by Murad ( 23 ), 3 series received a score of 6/8 ( 41 , 43 , 47 ) and 5 received a grade of 5/8 ( 1 , 42 , 44 46 ). Overall, the 23 studies were considered at high risk of bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the quality assessment described by Murad ( 23 ), 3 series received a score of 6/8 ( 41 , 43 , 47 ) and 5 received a grade of 5/8 ( 1 , 42 , 44 46 ). Overall, the 23 studies were considered at high risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…This strategy is in accordance with Protyniak et al ( 8 ), who demonstrated that the Xi platform can be used for multiquadrant surgery without repositioning the patient-side surgical cart. Recently two comparative studies ( 7 , 39 ) and two case series ( 46 , 47 ) evaluated the da Vinci Xi surgical system and multiquadrant surgery for TC, STC, and restorative TPC, using a totally robotic approach. All authors agreed that the robotic platform offered a significant advantage over the previous generations.…”
Section: Discussionmentioning
confidence: 99%
“…Nine comparative studies and 3 cases series of robotic IPAA where the proctectomy was performed robotically have been published to date. 7–15…”
Section: Proctectomymentioning
confidence: 99%
“…They also advocated specifically for the use of robotic stapler which allows the surgeon to control the rectal transection and may reduce the risk of anastomotic leak and rectal cuff problems. 15…”
Section: Total Proctocolectomymentioning
confidence: 99%
“…Multiple case series have examined the short- and intermediate-term outcomes of robotic STC, TPC/IPAA, and completion proctectomy/IPAA for UC, demonstrating that these approaches are safe and feasible, with shorter length of stay, earlier stoma function, less blood loss, low-leak rates, and equal morbidity and mortality to their laparoscopic counterpart operations. 15 The following pages describe our technique and experience with robotic STC and end ileostomy in the urgent setting, as well as robotic IPAA creation (stage 2 of the three-stage procedure), as well as the robotic experience with TPC for UC.…”
mentioning
confidence: 99%